Thực trạng tham gia của cha mẹ vào hoạt động hướng nghiệp và phân luồng học sinh trung học cơ sở trên địa bàn Hà Nội - Nguyễn Đức Sơn, Nguyễn Đức Sơn; Lê Minh, Nguyệt; Trần Anh Khôi, Trần Anh Khôi (Tạp chí Giáo dục, 2026)
The research was conducted on a sample of 540 parents of 9th-grade students from 38 secondary schools in Hanoi, aiming to identify the current situation and difficulties faced by parents when participating in career guidance and streaming activities at junior high schools. The primary research method was a questionnaire consisting of 27 items, designed on a 3-point Likert scale. The Cronbach’s Alpha reliability coefficient of the scale was 0.879, meeting scientific reliability standards. The survey results show that the dominant trend in parents’ awareness, attitudes, and actions regarding career orientation for their children is to continue cultural education at the high school level, aligned with their children’s aspirations, determination, and family conditions. Pursuing vocational training immediately after secondary high school is the perception and action of very few parents during the career counseling process for their children. Parents have participated, cooperated, and supported career guidance activities organized by the school, although this remains limited. However, they have performed quite well in orienting their children within the family setting. Many parents are facing difficulties, including in their daily relationships and communication with their children; in understanding their children’s psychology, tendencies, and aptitudes; and in their knowledge of the occupational system and methods for counseling their children. Based on the practical survey results, several directions for solutions can be suggested to enhance the effectiveness of parental involvement in career guidance and streaming activities at secondary schools in Hanoi.